If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x = 6x + 72 Reorder the terms: 7x = 72 + 6x Solving 7x = 72 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 7x + -6x = 72 + 6x + -6x Combine like terms: 7x + -6x = 1x 1x = 72 + 6x + -6x Combine like terms: 6x + -6x = 0 1x = 72 + 0 1x = 72 Divide each side by '1'. x = 72 Simplifying x = 72
| 5/3x+1/3x=211/3+7/3x | | 392/2 | | 1/12+3/8y=5/12 | | 5x+26(x-2)=103 | | 5(5x+22)=5 | | 4x-45=x^2 | | derp= | | KLN=9x-7 | | -(3a+4a-6)+2(9a+3)+3(-8a)= | | 2(11m-10)+6m=-6(-6m+2)-8 | | 13m-5=4m | | 784/2 | | 4(2x-5y)=-13 | | 4.3(g-7)=2(10+g) | | N+(n+1)=-389 | | 0.15y+0.08(y+7000)=1480 | | 7f-2(f+8)=29 | | r^2+8r-29=0 | | 10+6X-3= | | 6.5+j=12 | | x+3=7x-35 | | c(2c+3)+c-3(7+4c)= | | 2c-15=c+4 | | 4x+x+4x+x+5=180 | | 7+3/7+1/4-5-1/14 | | 2(11m-10)+6=-6(-6m+2)-8 | | 6x+9x=14x | | 40k+80k=30k+90 | | 6t+1/6=t+4/12+t-2/12 | | -5(6n-4)+30n= | | 65x+2=933 | | 2d-5/2=5d+2/9 |